Transformation towards sustainable business models in production : a case study of a 3D printer manufacturer - Ali Shah, Shahban (Array, 2020)
A global transformation from Industry 4.0 towards Industry 5.0 will soon take place. Such transformations are intrinsic to human and sustainable value creation. An increasing number of companies, recognising this imminent trend, will need to transform their current classical, solely profit-oriented business models into sustainable business models that also target human, social, and environmental aspects. Various frameworks already exist that support the design of sustainable business models. Practical applications of these frameworks and research on the transformation process in the production domain, which places a special focus on small and medium enterprises, is still scarce. This paper presents the first results from a sustainable business model transformation project on a European SME, which produces 3D printers. The research method applies a single case study design. The study was based on publicly available information and qualitative data, obtained through interviews and workshops carried out on an executive management level.